Entrepreneurship as endogenous development potential of communes in the Świętokrzyskie Province - Lipa, Adrian (Przedsiębiorczość jako endogeniczny potencjał rozwoju gmin województwa świętokrzyskiego, 2019)
In Poland are visible development disparities between municipalities. The aim of the article is to assess the significance of entrepreneurship in regional development and to determine its spatial diversity in the Świętokrzyskie Voivodeship (province) using a synthetic measure. The analysis was carried out in 102 communes of the Świętokrzyskie province for 2010-2017. The Si entrepreneurship measure in 2010 ranged from 0.28 to 0.78 and in 2017 from 0.32 to 0.86 and the OE development measure ranged from 0.35 to 0.83 in 2010 and from 0.21 to 0.78 in 2017. The level of entrepreneurship was influenced by: the level of unemployment and of employees, of business entities, of natural persons conducting economic activity and the infrastructure. The best indicator of entrepreneurship is in the cities of Kielce, Sandomierz, Skarżysko-Kamienna, Ostrowiec Św., with a developed industrial function. At the other end there were: Waśniów, Michałów, Koprzywnica, Klimontów − with agricultural, function
Biblioteka Regionalisty, 2019, Nr 19, s. 100-114
Keywords: Dolny Śląsk